Acute Type A Dissection during Pregnancy with Marfan's Syndrome - Heim, Christian; Müller, Philipp; Weyand, Michael; Harig, Frank (Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Marfan's syndrome (MFS) is a connective tissue disorder, caused by a mutation in the FBN-1 gene and affecting multiple organ systems including the vascular system. During pregnancy, women with MFS have an increased risk of aortic dissection due to changes in the cardiovascular system.
CRIS-Team WoS Importer:2021-04-02